2022
DOI: 10.1111/ced.15357
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox: key pointers for dermatologists

Abstract: The current monkeypox epidemic is a major public health concern as the global outbreak continues to grow. We present a case report to highlight the salient points for dermatologists. Human monkeypox is a zoonosis caused by monkeypox virus, belonging to the Orthopoxvirus genus and is a close relative of the variola virus. Pleomorphic skin lesions appear ranging from macules, papules, vesicles, pustules, some of which may appear umbilicated before crusting over. Dermatologists play a key role in early recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The majority of cases of mpox infection reasonably concluded by review authors to have resulted from a single transmission route occurred through direct physical sexual contact (13, 14, 18, 20, 22, 23, 25, 26, 27, 33, 34, 36, 37, 39, 40, 42, 44, 45, 47, 48, 51, 58, 59, 60, 61, 63, 64, 65, 67, 68, 71, 72, 78, 79, 83, 85, 86, 87, 88, 92, 93, 96, 97, 103, 104, 105, 106, 107, 109, 110, 111, 112, 114, 115, 119, 126) (Table 4). Where they could identify a single route of human-to-human transmission resulting in mpox infection, investigators reported no cases in which inhalation could reasonably have been the singular mode of mpox virus transmission (Table 4).…”
Section: Number Of Incident Cases By Route Of Transmissionmentioning
confidence: 97%
See 3 more Smart Citations
“…The majority of cases of mpox infection reasonably concluded by review authors to have resulted from a single transmission route occurred through direct physical sexual contact (13, 14, 18, 20, 22, 23, 25, 26, 27, 33, 34, 36, 37, 39, 40, 42, 44, 45, 47, 48, 51, 58, 59, 60, 61, 63, 64, 65, 67, 68, 71, 72, 78, 79, 83, 85, 86, 87, 88, 92, 93, 96, 97, 103, 104, 105, 106, 107, 109, 110, 111, 112, 114, 115, 119, 126) (Table 4). Where they could identify a single route of human-to-human transmission resulting in mpox infection, investigators reported no cases in which inhalation could reasonably have been the singular mode of mpox virus transmission (Table 4).…”
Section: Number Of Incident Cases By Route Of Transmissionmentioning
confidence: 97%
“…114 studies reported cases of human-to-human mpox as a result of transmission (13126). 39 studies were conducted prior to the 2022 outbreak (15, 16, 19, 21, 24, 31, 32, 35, 38, 43, 46, 49, 50, 53, 54, 55, 56, 62, 66, 69, 73, 74, 76, 77, 80, 81, 82, 83, 95, 99, 100, 101, 102, 116, 117, 120, 123, 124, 125) and 75 studies were published during 2022 (13, 14, 17, 18, 20, 22, 23, 25, 26, 27, 28, 29, 30, 33, 34, 36, 37, 39, 40, 41, 42, 44, 45, 47, 48, 51, 52, 57, 58, 59, 60, 61, 63, 64, 65, 67, 68, 70, 71, 72, 75, 78, 79, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, <...…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The region of acquisition of infection was reported as follows: 37 studies from Africa [ 15 , 19 , 21 , 24 , 31 , 32 , 35 , 38 , 43 , 49 , 50 , 53 56 , 62 , 66 , 69 , 73 , 74 , 76 , 77 , 80 83 , 90 , 95 , 99 102 , 116 , 120 , 123 125 ], 1 study from the Eastern Mediterranean Region [ 121 ], 48 studies from Europe [ 13 , 14 , 18 , 20 , 22 , 23 , 25 29 , 33 , 36 , 37 , 39 , 40 , 42 , 44 , 45 , 47 , 48 , 51 , 52 , 57 , 58 , 60 ,…”
Section: Review Stage Two: Transmission Route Of Mpox Virusmentioning
confidence: 99%